Basic research for resurrection of extinct animals by somatic cell nuclear transfer - 加藤, 博己; カトウ, ヒロミ (近畿大学, 2013)
研究成果の概要（和文): 現有するマンモス軟組織のDNAの状態の解析と, 骨髄組織からの体細胞核の回収方法の開発を行った. その結果, 骨髄組織からの効率の良い体細胞核の回収方法の開発に成功した. また, ロシア連邦サハ共和国から, 更に保存状態の良いマンモスの皮膚・筋肉・皮下組織および骨髄組織の入手に成功した. さらに, 異種間核移植の際に再構築胚の発生能力を改善させるために核ドナー細胞と同種のミトコンドリアの共注入を試みたが, 再構築胚の発生能力の改善には至らなかった. 研究成果の概要（英文): The analysis of the conservation state of existing mammoth soft tissue (skin, muscle and bone marrow) by PCR and the development of the method to collect somatic cell nuclei from bone marrow were examined. In results, we succeeded to develop the efficient method to collect somatic cell nuclei from bone marrow. Also we succeeded to have new, well conserved mammoth's skin, muscle, hypodermis and bone marrow from Sakha (Yakutia) Republic. Furthermore, to improve developmental ability of reconstructed embryos, we tried to co-inject mitochondria which derived from cells of same species with donor cell nucleus. However the developmental ability of reconstructed embryos was not improved. 研究種目：基盤研究(C); 研究期間：2011 ～ 2013; 課題番号：23580395; 研究分野：農学; 科研費の分科・細目：畜産学・獣医学、応用動物科学 Research Paper application/pdf research report